Analysis of Continuous Bioadsorptive Removal of Cadmium in the Light of Circular Economy and Sustainability. (June 2022) - Basu, Mousumi; Guha, Arun K.
Abstract: The presented study is an experimentation on bioadsorption of cadmium on lentil husk (LH) stacked in fixed bed column reactor. Here the concept of circular economy is integrated to demonstrate its compliance with biological adsorption. In addition sustainability evaluation of the work has been done with respect to environmental, economical and executional procedure. As regard to experimentation adsorption capacity, percentage adsorption and breakthrough time all found to be dependent on the variation of design parameters. Sorbate (cadmium) concentration in treated effluents was inversely proportional to bed height and directly related to flow rate owing to prolonged interaction with metal binding sites. Adsorption capacity (164.25 mg g −1 ) peaked up at highest feed concentration due to formation of concentration gradient, overcoming the resistance offered during transfer of solute. Desorption was fruitful (up to ~96%) and the fixed bed regained its performing capacity successively. Industrial effluents were reclaimed with high accuracy for considerable duration. Graphical abstract: Unlabelled Image Highlights: Dynamic adsorption of cadmium was done in fixed bed column reactor. Reactor efficiency was found to be depended upon proper optimization of design parameters. Cadmium bearing industrial effluents were cleaned with high capability. Compliance of the treatment method to the idea circular economy and sustainability issues were established.